Be true to your school : a diary of 1964 (c, 2010)
The cultural cataclysms of the sixties were a far-distant noise in 1964, the year the Beatles appeared on "The Ed Sullivan Show," the year Greene had his first beers, and one of his friends lost his virginity.
Keywords: Greene, Bob. Journalists -- United States -- Biography. High school students -- United States -- Biography